2012
DOI: 10.1108/00330331211204557
|View full text |Cite
|
Sign up to set email alerts
|

From LAMP to Koha: case study of the Pakistan legislative assembly libraries

Abstract: Purpose -This paper aims to elaborate the library data migration process from LAMP (Library Automation Management Program) to the open source software Koha's (2.2.8 Windows based) Pakistani flavour PakLAG-Koha in six legislative assembly libraries of Pakistan. Design/methodology/approach -The paper explains different steps of the data migration from one ILM (integrated library management system) to a new ILM in six libraries over the course of three months. Qualitative research methods, i.e. direct observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Such studies have been published on open source ILS (e.g. Bissels and Chandler, 2010;Genoese and Keith, 2011;Shafi-Ullah and Qutab, 2012), open source digital libraries (e.g. Bindu et al, 2010;Doctor, 2008;Stanger and McGregor, 2007), and open source discovery interfaces (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have been published on open source ILS (e.g. Bissels and Chandler, 2010;Genoese and Keith, 2011;Shafi-Ullah and Qutab, 2012), open source digital libraries (e.g. Bindu et al, 2010;Doctor, 2008;Stanger and McGregor, 2007), and open source discovery interfaces (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The purpose of these studies, in the case of adoption and development, was to inform the wider library community of the benefits that came from such a move (e.g. Doctor, 2007;Mah and Stranack, 2005;Shafi-Ullah and Qutab, 2012). Given the fact that OSS is a relatively recent development in the library world, and many librarians may be concerned about the reliability of these products (Payne and Singh, Open source software research 2010), it is not surprising that studies would be published detailing real, concrete benefits resulting from implementation of OSS.…”
Section: Distribution Of Articles By Topicmentioning
confidence: 99%
“…Several studies examined the adoption of the Koha open-source library management system for the respective libraries using data migration (House, 2016; Kampa and Kaushik, 2019;Keast, 2011; Ponelis and Adoma, 2018); all of these adoptions have gone through challenging and stressful processes. On the other hand, a few studies reported on the incompatibilities, data conversion issues, subfield problems, technical concerns, data migration issues and implementation problems of Koha (Makori and Osebe, 2016;Omeluzor et al , 2012; Shafi‐Ullah and Qutab, 2012; Todd, 2018; Walls, 2011).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The main features of PakLAG-Koha include the accommodation of regional languages of Pakistan, online keyboards in regional languages and a reporting module to meet local needs. The other important feature which is increasing the popularity of PakLAG-Koha over the OSS Koha is the availability of the PakLAG support team that has representatives all over the country (Shafi-Ullah and Qutab, 2012).…”
Section: Adoption Of Open Source Library Softwarementioning
confidence: 99%